Phonetic Reality of Plosive Consonants and Fricative Minangkabau Language in Bengkulu City - Dina Putri Juni Astuti; Susi Seles; Nelda Sari Siregar; Andre Taulani (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The Minangkabau language is unique, having 19 consonant phonemes in the vocabulary used in daily communication. The existence of phonemes indirectly affects the meaning and shift of the original sound. This is due to the reduction of consonant phonemes when young Minangkabau speakers tend to absorb the consonant system of Indonesian or their local environmental language, rather than Minangkabau. Thus, this study aims to: 1) describe the phonetic reality of Minangkabau plosive consonants in Bengkulu City and 2) describe the phonetic reality of Minangkabau fricative consonants in Bengkulu City. The research method used is qualitative descriptive. The research data was in the form of native Minang speech in Bengkulu City with 50 samples based on 4 criteria: age > 60 years, 50-60 years, 25-50 years and < 24 years. Data collection techniques are in the form of interviews and recordings as well as documentation. The results of this study were obtained 6 plosive consonant phonemes, namely: p/, /b/, /t/, /d/, /k/, and /g/ and 3 fricative consonant phonemes, namely: phonemes /s/, /h/ and /f/ in the daily speech of the Minangkabau people which have similarities with the structure of the Malay language. The conclusion of this study is that the plosive consonants and fricative consonants of the Minangkabau language have been proven to appear productively in various word positions, with the phonological structure of Minangkabau still functioning consistently in daily speech practice. Illustrating that the Minangkabau community in Bengkulu City still maintains its strong phonological identity and pronunciation system with a relative, stable, conservative and consistent sound system.